Pengaruh Kompensasi, Lingkungan Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan KSU Prima Gratiha Sejahtera Lombok - Bonefasius Philipus Ngangkat; I Gusti Gede Narung (Kredibel: Jurnal Ilmiah Manajemen, 2026)
This study aims to examine the effect of compensation, work environment, and job satisfaction on employee performance at Koperasi Serba Usaha Prima Grathia Sejahtera Lombok. This research uses an associative method with data collection techniques including questionnaires, interviews, and documentation. The population consists of 54 active employees, and the sampling technique used is a saturated sample. Data analysis was conducted using multiple regression with SPSS version 25. The results show that compensation (X1), work environment (X2), and job satisfaction (X3) significantly affect employee performance. Compensation has a significant effect as indicated by tcount 2.067 > ttabel 2.007 with a significance level of 0.044 < 0.05. The work environment also has a significant effect with tcount 2.578 > ttabel 2.007 and a significance level of 0.013 < 0.05. Job satisfaction has a significant effect with tcount 3.397 > ttabel 2.007 and a significance level of 0.001 < 0.05. Simultaneously, compensation, work environment, and job satisfaction significantly affect employee performance with Fcount 90.791 > Ftabel 2.79 and a significance level of 0.000 < 0.05. These findings suggest that improving compensation, work environment, and job satisfaction can enhance employee performance.